Penggunaan Media Game Kahoot dalam Kalkulus I untuk Meningkatkan Minat dan Hasil Belajar Mahasiswa - Nur'aini Muhassanah; Riski Aspriyani; Mutia Mutia (ARITHMETIC: Academic Journal of Math, 2023)
The goal of this study is to use Kahoot Game media in learning to enhance student learning outcomes and engagement in Calculus I courses. The months of September through December 2022 were used for this study. This form of study was called Classroom Action Research and it was divided into two cycles, each of which included four stages: planning, action, observation, and reflection. This study focused on 12 first-semester mathematics majors who took Calculus I courses during the 2022–2023 school year. Observations, tests, and questionnaires were employed as the data gathering methods. The results of this study were 1) the class average score showed an improvement in scores on the pretest and posttest in each cycle, which increased the outcomes of learning attainment; 2) enhancing student learning motivation in Calculus I classes when the pre-cycle, cycle I, and cycle II average scores are used. The criteria for student interest in learning outcomes, which before the research, students were included in the criteria of good enough and good criteria, demonstrate this. Students were added to the good and very good criteria once the action was taken.